IMPACT OF CHESS LEARNING ON PROCESSING SPEED OF SCHOOL-GOING CHILDREN - JOSEPH, EBENEZER; Easvaradoss, Veena; Chandran, David; Jain, Sweta; Paul, Ashwath (Advances in Social Sciences Research Journal, 2018)
Processing speed is one of the measures of cognitive efficiency. It refers to the ability to automatically and fluently execute relatively easy or overlearned cognitive tasks, especially when high mental efficiency is required. Contemporary research has shown that the speed of information processing is dynamically associated with mental capacity, reading performance, and development and reasoning by the conservation of cognitive resources and the efficient use of working memory. While the impact of chess training on intelligence and academic performance has been unequivocally established, its impact on processing speed needs to be researched. This study, funded by the Cognitive Science Research Initiative, Department of Science and Technology, Government of India, analyzed the effect of 1-year chess training on the processing speed of children. A pretest–posttest with control group design was used, with 88 children in the experimental group and 90 children in the control group. The sample was selected from children studying in four city schools (grades 3–9), which included both genders. The experimental group underwent weekly chess training for 1 year, while the control group was involved in extracurricular activities. Processing speed was measured by two subtests of Wechsler Intelligence Scale for Children (WISC-IV India), namely Coding and Symbol Search. The training methodology comprised Winning Moves Chess Learning Program with the demonstration board, on-the-board playing and training, chess exercise through workbooks, and working with chess software. Analysis revealed significant gains in processing speed in the experimental group compared with the control group. The present study clearly establishes a link between chess training and processing speed. Enhancing processing speed in children is especially important because of its relationship to other cognitive and academic performance indicators.